Do painters need their whole brain to excel?. Issue 3 (3rd May 2020) - Fornazzari, Luis; Haladyn, Julian; Toledo, Tamara; Leggieri, Melissa; Friszberg, Isabel; Barfett, Joseph; Bharatha, Aditya; Munoz, David; Schweizer, Tom; Fischer, Corinne E
ABSTRACT: Skilled professional artists are sometimes able to maintain their talents while other cognitive functions deteriorate due to brain diseases. The objective of this study is to asses the preserved artistry of a professional painter in spite of the presence of strokes affecting brain areas implicated in art expression. She had a neurologic evaluation and brain imaging after the stroke; painter-curators analyzed and compared the painter's pictorial artwork created before and after the stroke. In spite of cerebellar, visuospatial, motor, cognitive, and functional deficits likely related to strokes affecting bilateral cerebellar, left occipital, and right temporal-occipital areas, the patient was able to maintain most of their artistic painting skills.. After a short period of functional recovery, our patient showed discrepancy among their impaired cerebellar cerebral functions in day activities and their preserved painting abilities.